2016
DOI: 10.7196/samj.2016.v106i4.10671
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted hospital-wide intervention increases hand hygiene compliance

Abstract: Background. Hand hygiene is an important and basic practice that should be used by all healthcare staff to protect both themselves and their patients against infection. Unfortunately hand hygiene compliance remains poor. Objective. To show an improvement in hand hygiene compliance using a multifaceted approach. Methods. This was a quasiexperimental pre-post intervention study design with a number of standardised interventions to promote hand hygiene. The World Health Organization hand hygiene multimodal (five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…In addition, compliance rates for “before” related indications were promoted after intervention, such as “before touching a patient” and “before clean/aseptic procedures”. These findings revealed that HCWs were inclined to wash their hands to protect themselves rather than protect patients from potential infection, which was noted in previous studies [ 31 , 32 ]. As for indication “after touching patient surroundings”, HH opportunities with this indication were most commonly associated with lower levels of compliance than following direct patient contact [ 33 ].…”
Section: Discussionsupporting
confidence: 71%
“…In addition, compliance rates for “before” related indications were promoted after intervention, such as “before touching a patient” and “before clean/aseptic procedures”. These findings revealed that HCWs were inclined to wash their hands to protect themselves rather than protect patients from potential infection, which was noted in previous studies [ 31 , 32 ]. As for indication “after touching patient surroundings”, HH opportunities with this indication were most commonly associated with lower levels of compliance than following direct patient contact [ 33 ].…”
Section: Discussionsupporting
confidence: 71%
“…According to the Global Human Development Index (HDI) (41) , approximately 85% (21/25) of the countries in which the studies included in this review occurred have a very high or high HDI (4)(5)(7)(8)13,(19)(20)(21)(23)(24)(25)(26)(27)(28)(29)(30)(31)(34)(35)(36)(37) . With respect to the medium and low HDI countries (4/25) (18,22,(32)(33) , all had a pre-intervention HH compliance of less than 30%, and a post-intervention compliance of less than 50%, except a study (18) (1/4) that reached 57% after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to greater sustainability over time in HH compliance, interventions that presented educational actions that included the five components of the multimodal strategy maintained higher post-intervention compliance rates (7,8,13,(24)(25)27,36) . The self-sustaining average among these studies was 83%, and some factors, besides those related to infrastructure, can be considered as responsible for such results, such as intervention time, which ranged from three months to one year or more, lectures and workshops used concomitantly by means of practical elucidations, immediate and/or weekly feedback, monthly reports to team leaders and managers, professional effort recognition, placards at strategic locations, screenshots on computers, and institution's commitment to security environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only 67% of participants believed that it was necessary to wash hands after cerumen management, 88% of participants reported that they washed their hands after cerumen management. However, this is still concerning, as cerumen can be considered an infectious substance and may lead to opportunistic infections, such as methicillin-resistant Staphylococcus aureus (MRSA) (Kemp & Bankaitis, 2000; Patel, Engelbrecht, McDonald, Morris, & Smythe, 2016).…”
Section: Discussionmentioning
confidence: 99%